Strategi Manajerial Kepala Sekolah dalam Mengembangkan Literasi Islami sebagai Program Unggulan untuk Meningkatkan Penerimaan Siswa Baru (JURNAL ILMIAH TUT WURI HANDAYANI, 2025)
The primary objective of this study is to provide an in-depth explanation of the managerial strategies implemented by school principals in designing and developing Islamic literacy as a flagship program aimed at increasing new student enrollment. This program has been consistently applied each year, not only to strengthen Islamic character education but also to serve as a competitive differentiation strategy to attract public interest. A qualitative case study approach was employed to explore the principal's role through in-depth interviews, field observations, and administrative document analysis. The findings indicate that the principal plays a strategic role in all phases of management: planning, organizing, implementation, and evaluation. Specific strategies include integrating Islamic values into the curriculum, internalizing Islamic culture through daily prayer memorization, short Qur'anic surahs, hijaiyah literacy habits, worship practices, and the use of Islamic reading materials. Active parental and community involvement further strengthens the systemic implementation of the program. The Islamic literacy program has had a significant impact on enhancing the school’s image and increasing student registration annually. The study concludes that value-based management strategies rooted in Islamic principles hold great potential in improving the competitiveness of Islamic educational institutions in today’s dynamic environment. Keywords: management strategy, school principal, Islamic literacy, flagship program, student enrollment